Preparation, Characterization, and Application of Citrate-Functionalized Cobalt-Doped Iron Oxide Nanoparticles for Rhodamine Dye and Lead Ion Sequestration - Sangeetha Jayakumar; Barid Baran Lahiri; Arup Dasgupta (Magnetochemistry)
The toxicity of hazardous dyes like rhodamine B and heavy metal ions like lead warrants the need for wastewater remediation. We describe here the functionalization of cobalt-doped iron oxide (Co0.1Fe2.9O4) magnetic nanoparticles (MNPs) with citrate moieties for the effective sequestration of rhodamine B dye and lead ions from contaminated water. Citrate-functionalized MNPs are prepared using a co-precipitation technique. For the uncoated MNPs, the hydrodynamic diameter and zeta potential are found to be 21 nm and ~45 ± 3.1 mV, respectively. The hydrodynamic diameters are found to increase to ~51, ~59, and ~68 nm for the MNPs functionalized with ~20, ~40, and ~60 mg/mL of citrate, respectively, whereas the corresponding zeta potentials are found to be ~−27.95 ± 3.5 mV, ~−32.5 ± 3.6 mV, and ~−33.9 ± 3.5 mV, respectively. The chemisorption of the citrate moieties over the MNPs cause the zeta potential to be negative, a phenomenon which is further verified from the citrate-specific absorption bands in the Fourier transform infrared (FTIR) spectra of the surface-functionalized MNPs. UV-visible spectrophotometry is employed to probe the MNP-aided elimination of rhodamine B dye and lead ions from aqueous media, where the absorption bands at ~554 nm and ~375 nm (for lead (II)-5-dimercapto-1,3,4-thiadiazole chelate) are utilized for quantitative analyses. These citrate-functionalized nanoparticles are found to successfully remove the toxic rhodamine B dye and lead ions from water, with removal efficiencies of ~93.7 ± 2.6% and ~90 ± 2.4%, respectively. The unbound -COO− functional groups of the citrate-functionalized MNPs electrostatically interact with the cationic rhodamine B dye or lead (II) ions, thereby leading to the adsorption onto the surface-functionalized MNPs and the subsequent magnetic-field-assisted removal. The experimental findings show the efficacy of the citrate-functionalized cobalt-doped iron oxide MNPs for the sequestration of dye pollutants and lead ions from contaminated water.